Identification of PPREs and PPRE associated genes in the human genome: insights into related kinases and disease implications - Saha, Pritha; Talwar, Priti (Frontiers in Immunology, 2024)
Introduction “Peroxisome Proliferator-Activated Receptors” (PPARs) belong to the class of transcription factors (TF) identified as Nuclear Receptors (NR). Upon activation by peroxisome proliferators (PPs), PPARs modulate a diverse range of genes, consequently regulating intra-cellular lipid metabolism, glucose uptake, apoptosis, and cell proliferation. Subsequent to the heterodimerization of Retinoid X Receptors (RXR) with PPARs induced by the binding of activators to PPARs, facilitates the binding of the resulting complex to Peroxisome Proliferator-Activated Receptors Response Elements (PPRE), with a consensus sequence 5’AGGTCANAGGTCA-3’, and regulate the transcription of the targeted genes. Methods A comprehensive screening of PPRE within the whole human genome was performed using the Genome Workbench and UCSC Genome Browser to find the associated genes. Subsequently, the kinase subset was isolated from the extracted list of PPRE-related genes. Functional enrichment of the kinases was performed using FunRich, ToppGene, and ShinyGO. Network analysis and enrichment studies were then further performed using NDEx to elucidate these identified kinases' connections and significance. Additionally, the disease association of the PPRE kinases was analyzed using DisGeNET data in R studio and the COSMIC dataset. Results A comprehensive analysis of 1002 PPRE sequences within the human genome (T2T), yielded the identification of 660 associated genes, including 29 kinases. The engagement of these kinases in various biological pathways, such as apoptosis, platelet activation, and cytokine pathways, revealed from the functional enrichment analysis, illuminates the multifaceted role of PPAR in the regulation of cellular homeostasis and biological processes. Network analysis reveals the kinases interact with approximately 5.56% of the Human Integrated Protein-Protein Interaction rEference (HIPPIE) network. Disease association analysis using DisGeNET and COSMIC datasets revealed the significant roles of these kinases in cellular processes and disease modulation. Discussion This study elucidates the regulatory role of PPAR-associated genes and their association with numerous biological pathways. The involvement of the kinases with disease-related pathways highlights new potential for the development of therapeutic strategies designed for disease management and intervention.